Evaluation of the Implementation of the Smoke-Free Zone Policy in DKI Jakarta Province - Arga Lintong; Nurliah Nurdin; Megandaru Widhi Kawuryan (Sean Institute, 2025)
This study aims to analyze and evaluate the implementation of the Smoke-Free Area (KTR) policy in DKI Jakarta Province. The objectives of this study are to assess the extent to which this policy is implemented effectively and efficiently, and to identify factors that influence compliance with the policy in the field. This study uses Dunn's (2003) policy evaluation theory, which includes six main criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The approach used in this study is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results show that although this policy has shown some progress, such as increased public awareness of the importance of a smoke-free environment, significant challenges remain, particularly in terms of inconsistent law enforcement and low levels of compliance in several sectors, such as public transportation and public places. This evaluation also highlights the need for increased oversight, community engagement, and the provision of smoking facilities that meet standards. Furthermore, although resource management is quite good, increased budget and human resources are essential to strengthen policy implementation. This study proposes that the DKI Jakarta Provincial Government improve inter-agency coordination, strengthen oversight through technology, and expand educational campaigns to ensure the overall success of the KTR policy. In this regard, stricter law enforcement and continuous evaluation are key to achieving optimal policy objectives. This research contributes to our understanding of the implementation of the KTR policy in Jakarta and strategies for improving it for a healthier future.